2010
DOI: 10.1038/hr.2010.251
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparathyroidism, arterial hypertension and aortic stiffness: a possible bidirectional link between the adrenal cortex and the parathyroid glands that causes vascular damage?

Abstract: P rimary hyperparathyroidism (PPTH) isgenerally thought to be a common endocrine disorder. However, it represents an uncommon endocrine cause of arterial hypertension, with a likely prevalence among hypertensive patients of less than 0.01%-an imprecise estimate because of the lack of prospective studies.However, between 56% and 80% of the patients with PPTH have high blood pressure (BP) and display hypertension-related target organ damage. On the basis of large studies from Scandinavia, a high rate of cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 10 publications
1
18
0
1
Order By: Relevance
“…As with hypertension, arterial stiffness has been previously linked to maladaptive RAAS activity and can be improved with RAAS blockade [55, 56], implicating the RAAS as one of several potential mediators of the adverse vascular phenotypes observed in PHPT. Other proposed mechanisms include indirect effects via hypertension and renal dysfunction, as well as direct effects of elevated PTH levels and/or the accompanying hypercalcemia [53, 57]. …”
Section: Calcium- Pth- and Vitamin D-mediated Control Of The Raasmentioning
confidence: 99%
“…As with hypertension, arterial stiffness has been previously linked to maladaptive RAAS activity and can be improved with RAAS blockade [55, 56], implicating the RAAS as one of several potential mediators of the adverse vascular phenotypes observed in PHPT. Other proposed mechanisms include indirect effects via hypertension and renal dysfunction, as well as direct effects of elevated PTH levels and/or the accompanying hypercalcemia [53, 57]. …”
Section: Calcium- Pth- and Vitamin D-mediated Control Of The Raasmentioning
confidence: 99%
“…9,10 Moreover, given the emerging evidence implicating hyperparathyroidism as a cardiovascular risk factor, 10 it could be that the high serum PTH found in this study contributes both to the excess cardiovascular damage and to the persistent hyperaldosteronism of PA patients. Therefore, the provoking findings of this study should prompt further research on a larger population of different ethnicities with the aim of conclusively proving whether raised PTH is a marker of APA.…”
Section: Perspectivesmentioning
confidence: 99%
“…Accordingly, there is an unmet need of a better strategy for selecting patients more likely to have an APA to be submitted to adrenal vein sampling (AVS). After the pilot reports of secondary hyperparathyroidism in patients with PA 2,3 and also with secondary aldosteronism attributed to congestive heart failure, [4][5][6] we and others recently documented an elevation of serum parathyroid hormone (PTH) levels in large cohorts of patients with confirmed PA. 7,8 These observations are of great interest given the adverse cardiovascular consequences of excess PTH, which is now appreciated as a cardiovascular risk factor, 9,10 and also because of the evidence that PTH can exert a secretagogue effect on aldosterone. In vitro studies consistently showed that PTH concentration-dependently increases aldosterone in rat, 11 bovine, and human dispersed adrenocortical cells 12,13 and enhanced the secretagogue effect of angiotensin II on aldosterone.…”
mentioning
confidence: 99%
“…4 Therefore, it would be expected to lower rather than to raise blood pressure. 5 The mechanisms by which excess PTH increases blood pressure remained obscure until Mazzocchi et al 6 reported that PTH stimulates in vitro the secretion of aldosterone from human adrenocortical cells in a concentrationdependent manner. These findings suggested that PTH acts as an aldosterone secretagogue that might be involved in causing human PA.…”
mentioning
confidence: 99%